(untitled) (LIS TODAY, 2021)
The study tries to make awareness among the library and information science professionals to use Google products/services for enhancing the library and information services at zero investment. The paper reveals the products/services of Google which can be utilized in libraries and information centers for efficient working. The paper also describes how librarians and library staff can use google products/services for fulfilling various tasks and objectives of library and information centers. The researcher has given several suggestions to library professionals regarding the use of google products/services in library and information centers.